2019
DOI: 10.25095/mufad.607189
|View full text |Cite
|
Sign up to set email alerts
|

İslami ve Geleneksel Endeks Performanslarının Karşılaştırılması Üzerine Bir Araştırma

Abstract: Islamic finance has become an important component of the international financial system. Although the very recent experience of Islamic finance was 40 years ago it is growing by 30% since 2000. Despite the growing interest in Islamic finance and Islamic capital markets, there are a few empirical studies that examine the performance of Islamic equity investing in the literature. As can be seen from the literature, the relations between Islamic and conventional indices vary according to the period and country of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Comparing the performances of Islamic and conventional Dow Jones and Morgan Stanley indices created for Turkey between 2005-2015, Ata and Buğan (2015), while using the ADF unit root test and causality analysis, found a strong causal relationship between the positive and negative shocks of the Dow Jones market indices during the crisis period under study. A similar study was conducted by Tükenmez et al (2019), in which the authors compared the return performances of Islamic and conventional indices from 2010 to 2019. They found that Islamic indices performed better than their counterparts.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Comparing the performances of Islamic and conventional Dow Jones and Morgan Stanley indices created for Turkey between 2005-2015, Ata and Buğan (2015), while using the ADF unit root test and causality analysis, found a strong causal relationship between the positive and negative shocks of the Dow Jones market indices during the crisis period under study. A similar study was conducted by Tükenmez et al (2019), in which the authors compared the return performances of Islamic and conventional indices from 2010 to 2019. They found that Islamic indices performed better than their counterparts.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Many empirical studies have explored Islamic Indices' performance in different parts of the world, such as Tükenmez et al (2019), Aisjah andHadianto (2013), andJabeen et al (2018). Some studies that have focused on the performance of Islamic indices between different countries have found varying results.…”
Section: Literature Reviewmentioning
confidence: 99%